JEJAK ARSITEKTUR RUMAH ADAT SIWALUH JABU DI DESA BUDAYA LINGGA KABUPATEN KARO SEBAGAI WARISAN BUDAYA TAKBENDA (INTANGIBLE CULTURAL HERITAGE) - Muhammad Gilang Ramadhan; Wahyu Apriandi Batubara; Puput Handriani, Widia Lestari; Muhammad Ikhsan Harahap (STKIP Subang, 2025)
The purpose of this study is to analyze in depth the architectural legacy of the Karo traditional house, particularly Siwaluh Jabu in Lingga Cultural Village, as a cultural mirror embodying historical, philosophical, and social values, and to explore how its surviving local wisdom can be understood in the context of modern society. The study examines not only its architectural form but also the symbolic meanings it conveys, positioning Siwaluh Jabu as an intangible cultural heritage that integrates material and immaterial aspects. The research adopts a qualitative-descriptive method with an ethnographic and literature-based approach, drawing data from field observation, interviews with traditional leaders, and textual studies. This approach provides a comprehensive understanding of the relationship between architectural form and the social, religious, and ecological values still present in the community of Lingga Cultural Village. The findings reveal that the Karo traditional house functions not only as a dwelling but also as a symbol of collective identity, a space for social interaction, and a medium to foster solidarity. Its stilted structure and distinctive roof reflect ecological awareness and harmony with nature, while its spatial organization represents principles of deliberation, equality, and respect for ancestors. The significant novelty of this study lies in its integration of architectural and cultural perspectives, affirming that preservation should extend beyond physical conservation to revitalization of philosophical, social, and ecological values. This study thus contributes to raising awareness among society and policymakers on the importance of safeguarding Siwaluh Jabu as a living heritage that bridges tradition and modernity.